Dynamics in numbers of group-roosting individuals in relation to pair-sleeping occurrence and onset of egg-laying in European Bee-eaters Merops apiaster - Parau,LG; Kingma,SA; Weigl,SE; Dugdale,HL; Lessells,CM; Schroeder,J (Journal of Ornithology, 2017)
Sleeping in the nest at the beginning of the breeding season is common for birds nesting in cavities. Here, we report evidence that European Bee-eaters Merops apiaster sleep in pairs in the nesting burrow. In 3.2% of the nest checks, we found two individuals sleeping together. This behaviour ceased once hatching started. A decrease in the number of birds at a communal roost coincided with the incidences of pair-sleeping and initiation of egg-laying. Thus, checking the burrows of European Bee-eaters at the beginning of the breeding season increases the chance of observing pair-sleeping.